Female bullying among adolescents in Italy: A national mixed-method research - Antonietta De Vita; Giuseppe Burgio (University of Bologna, 2023)
The subject of bullying has received widespread academic attention, going back to pioneering studies in the 1970s. However, work in this area has tended to take a gender-neutral/male perspective that does not distinguish between male and female bullying. While retaining a dialogue with generalist literature on the subject, this article seeks to highlight the theoretical and political-social relevance of gender-specific and intersectional approaches when exploring the question of bullying between adolescent girls. Based on the study Il bullismo femminile a scuola. Un'indagine intersezionale mixed-method (Female bullying at school, an intersectional, mixed-method study) - conducted in medium-sized and large cities in northern, central and southern Italy - it proposes a theoretical-analytical framework in which to consider the phenomenon of female bullying in Italian schools.